Evaluación de la corrupción en el crecimiento económico desde el impacto de la competitividad en el periodo 2.013-2.015 en Colombia (2019)
Transparency in both institutionality and infrastructure, according to the importance of these pillars in the competition, the results are essential to achieve the best levels of competence not only at the departmental level but at the national level, in order to achieve a great advantage and likewise generate economic growth. Therefore, through Indexes such as the Departmental Competitiveness Index, carried out by the Private Competitiveness Council in conjunction with the Universidad del Rosario and the Open Government Index, it is about finding little transparency and possible corruption risks. It becomes one of the biggest problems in the trust and management of institutions such as the good quality of the infrastructure, especially the connectivity, of the country's departments.